Preoperative evaluation before MitraClip®: present and future perspective. (November 2014) - Salerno, Gemma; Schmidt, Frank Patrick; Bigazzi, Maurizio Cappelli; Sordelli, Chiara; Bianchi, Renato; Golino, Paolo; Calabrò, Paolo; Russo, Maria Giovanna; Calabrò, Raffaele; Pacileo, Giuseppe
ABSTRACT : Mitral regurgitation (MR) is the second most common heart valve disease worldwide. Currently, the management of MR is based on medical therapy (including biventricular pacing), surgery (mitral valve replacement or repair) and percutaneous therapy. However, in spite of guideline recommendations, 50% of individuals assessed in the Euro Heart Survey were not referred to surgical intervention due to comorbidities or real or perceived high risks for cardiac surgery; thus, in recent years, the focus of research has shifted to the development of percutaneous approaches to treat severe MR in order to restore valve function in a minimally invasive fashion. Among these techniques, the percutaneous mitral valve repair procedure using the MitraClip ® system (Abbott Vascular, IL, USA) is one of the most promising. Usually, patient selection for MitraClip implantation is based on careful echocardiographic assessment of valve disease; however, although definitive data are lacking, evidence is mounting for a multiparametric approach including the evaluation of the functional status of patients.